Single SnO2 Nanowire: field emission investigations - Joshi, D.; Joag, Dilip S.; Mulla, Imtiaz S.; Late, Dattatray J. (2016 29th International Vacuum Nanoelectronics Conference (IVNC), 2016)
The present work deals with the field emission study on multiple SnO2 nanowires synthesized by simple thermal evaporation method. For the realistic analysis of the Fowler Nordheim plot of the semiconducting SnO2, field emission behavior of a single nanowire is studied. A relevant model explaining the field emission mechanism from the single SnO2 nanowire is also proposed by the authors.
Keywords: SnO2 nanowire